Pengaruh Model Pembelajaran Team Games Tournament (TGT) Terhadap Keaktifan Belajar Siswa Padan Mata Pelajaran Ilmu Pengetahuan Sosial Di Sekolah Menengah Pertama Negeri 23 Pekanbaru - Sutra Aliza; Emilia Susanti (CV. ITTC INDONESIA, 2026)
This research aimed at finding out the effect of Team Games Tournament learning model toward student learning activeness on Social Science subject at State Junior High School 23 Pekanbaru. This research was instigated with the lack of student learning activeness, including students who were less able to seek information, ask questions, discuss, and express opinions. It was quantitative research with quasi experiment approach. All the eighth-grade students were the population of this research, and they were 329 students. The samples were 73 students, they were the eighth-grade students of class F and the students of class G. Observation, questionnaire, and documentation were the techniques of collecting data. The techniques of analyzing data were normality test, homogeneity test, hypothesis test (independent sample t-test), effect test (effect size), and N-Gain Score test assisted with SPSS 25 application. Based on the research findings and data analyses, there was a significant effect of Team Games Tournament (TGT) learning model toward student learning activeness on Social Science subject at State Junior High School 23 Pekanbaru. It was proven with the results of independent sample t-test that the score of tobserved was 3.507 higher than ttable 1.666, and the score of significance was 0.001 lower than 0.05. The mean of student learning activeness in the experimental group was higher (97.70) than the control group (94.75), and the effect size score 0.56 indicated that the effect was in moderate category. The results of N-Gain Score test also showed that the increase in student learning activeness in the experimental group was in high category with the mean 93.09%. So, it could be concluded that Ha could be accepted, and H0 was rejected.